IMPLEMENTASI OWASP ZAP UNTUK PENGUJIAN KEAMANAN SISTEM INFORMASI AKADEMIK - Gregorius Kusuma (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2022)
Information security is an important thing that must be considered for every individual and institution in order to avoid crime. Poor information systems can threaten the critical infrastructure of an organization. Problems with system security vulnerabilities or disruptions are widely scattered on the internet. Early detection of the weakness of a system is the initial solution in securing a system. Therefore we need an analysis of the vulnerability of a system that refers to the security standardization of the Open Web Application Security Project (OWASP) by performing an active scan. Website vulnerability analysis using the OWASP ZAP technique with the help of several security tools is able to determine the security level of a website based on the results of scans and tests that have been carried out where almost every test category is able to find vulnerabilities, although there are several categories that do not have vulnerabilities. The purpose of this study is to identify the vulnerabilities contained in the University Academic Information System website and conduct testing and analysis to determine the condition of the vulnerability of the University Academic Information System website using the Open Web Application Security Project (OWASP). The research method used as a website security parameter is OWASP Top-10 2021.